![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(x^2-25-\left(x+5\right)=0\Leftrightarrow x^2-25-x-5=0\Leftrightarrow x^2-x-30=0\)
\(\Leftrightarrow x^2+5x-6x-30=0\Leftrightarrow x\left(x+5\right)-6\left(x+5\right)=0\)
\(\Leftrightarrow\left(x-6\right)\left(x+5\right)=0\Leftrightarrow\left\{{}\begin{matrix}x-6=0\\x+5=0\end{matrix}\right.\) \(\Leftrightarrow\left\{{}\begin{matrix}x=6\\x=-5\end{matrix}\right.\) vậy \(x=6;x=-5\)
b) \(\left(2x-1\right)^2-\left(4x^2-1\right)=0\Leftrightarrow4x^2-4x+1-4x^2+1=0\)
\(2-4x=0\Leftrightarrow4x=2\Leftrightarrow x=\dfrac{2}{4}=\dfrac{1}{2}\) vậy \(x=\dfrac{1}{2}\)
c) \(x^2\left(x^2+4\right)-x^2-4=0\Leftrightarrow x^2\left(x^2+4\right)-\left(x^2+4\right)=0\)
\(\Leftrightarrow\left(x^2-1\right)\left(x^2+4\right)=0\Leftrightarrow\left\{{}\begin{matrix}x^2-1=0\\x^2+4=0\end{matrix}\right.\) \(\Leftrightarrow\left\{{}\begin{matrix}x^2=1\\x^2=-4\left(vôlí\right)\end{matrix}\right.\)
ta có : \(x^2=1\Leftrightarrow x=\pm1\) vậy \(x=1;x=-1\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Tìm x:
a) \(x^2-25-\left(x+5\right)=0\)
\(\Leftrightarrow x^2-x-30=0\)
\(\Leftrightarrow\)\(\left[\begin{array}{} x=6\\ x=-5 \end{array} \right.\)
b) \(\left(2x-1\right)^2-\left(4x^2-1\right)=0\)
\(\Leftrightarrow4x^2-4x+1-4x^2+1=0\)
\(\Leftrightarrow2-4x=0\)
\(\Leftrightarrow x=\dfrac{1}{2}\)
c) \(x^2\left(x^2+4\right)-x^2-4=0\)
\(\Leftrightarrow x^2\left(x^2+4\right)-\left(x^2+4\right)=0\)
\(\Leftrightarrow\left(x^2-1\right)\left(x^2+4\right)=0\)
\(\Leftrightarrow\)\(\left[\begin{array}{} x^2-1=0\\ x^2+4=0 \end{array} \right.\)
\(\Leftrightarrow\)\(\left[\begin{array}{} x=1\\ x=-1 \end{array} \right.\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: \(\Leftrightarrow-2x^2+4x+x-2-2x^2=0\)
=>5x-2=0
hay x=2/5
b: \(\Leftrightarrow\left(x^2-1\right)\left(x-3\right)+\left(4-x\right)\left(x^2-1\right)=0\)
\(\Leftrightarrow\left(x^2-1\right)\left(x-3+4-x\right)=0\)
=>(x-1)(x+1)=0
=>x=1 hoặc x=-1
c: \(\Leftrightarrow-x^2+2x-30=0\)
\(\Leftrightarrow x^2-2x+30=0\)
hay \(x\in\varnothing\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\left(x-2\right)\left(x^2+2x+7\right)+2\left(x^2-4\right)-5\left(x-2\right)=0\)
\(\Rightarrow\left(x-2\right)\left(x^2+2x+7\right)+2\left(x-2\right)\left(x+2\right)-5\left(x-2\right)=0\)
\(\Rightarrow\left(x-2\right)\left[x^2+2x+7+2\left(x+2\right)-5\right]=0\)
\(\Rightarrow\left(x-2\right)\left(x^2+2x+7+2x+4-5\right)=0\)
\(\Rightarrow\left(x-2\right)\left(x^2+4x+6\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}x-2=0\\x^2+4x+6=0\end{matrix}\right.\)
Ta có:
\(x^2+4x+6\)
\(=x^2+2.x.2+4+2\)
\(=\left(x+2\right)^2+2\)
Vì \(\left(x+2\right)^2\ge0\) với mọi x
\(\Rightarrow\left(x+2\right)^2+2\ge2\) với mọi x
\(\Rightarrow x^2+4x+6\) vô nghiệm
\(\Rightarrow x-2=0\)
\(\Rightarrow x=2\)
b) \(3x\left(x-1\right)+\left(x-1\right)=0\)
\(\Rightarrow\left(x-1\right)\left(3x+1\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}x-1=0\\3x+1=0\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=1\\x=-\dfrac{1}{3}\end{matrix}\right.\)
c) \(2\left(x+3\right)x^2-3x=0\)
\(\Rightarrow x\left[2\left(x+3\right)x-3\right]=0\)
\(\Rightarrow x\left(2x^2+6x-3\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}x=0\\2x^2+6x-3=0\end{matrix}\right.\)
Ta có:
\(2x^2+6x-3\)
\(=2\left(x^2+3x-\dfrac{3}{2}\right)\)
\(=2\left(x^2+2.x.\dfrac{3}{2}+\dfrac{9}{4}-\dfrac{9}{4}-\dfrac{3}{2}\right)\)
\(=2\left(x+\dfrac{3}{2}\right)^2-\dfrac{15}{2}\)
Vì \(2\left(x+\dfrac{3}{2}\right)^2\ge0\) với mọi x
\(\Rightarrow2\left(x+\dfrac{3}{2}\right)^2-\dfrac{15}{2}\ge-\dfrac{15}{2}\) với mọi x
\(\Rightarrow2x^2+6x-3\) vô nghiệm
\(\Rightarrow x=0\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(5\left(x+7\right)-12x=15\)
\(5x+35-12x=15\)
\(-7x=15-35\)
\(-7x=-20\)
\(x=\frac{20}{7}\)
vay \(x=\frac{20}{7}\)
b) \(x^2-25-\left(x+5\right)=0\)
\(x^2-5^2-\left(x+5\right)=0\)
\(\left(x-5\right)\left(x+5\right)-\left(x+5\right)=0\)
\(\left(x+5\right)\left(x-5-1\right)=0\)
\(\left(x+5\right)\left(x-6\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x+5=0\\x-6=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=-5\\x=6\end{cases}}\)
vay \(\orbr{\begin{cases}x=-5\\x=6\end{cases}}\)
c) \(\left(2x-1\right)^2-\left(4x^2-1\right)=0\)
\(\left(2x-1\right)\left(2x-1\right)-\left(\left(2x\right)^2-1^2\right)=0\)
\(\left(2x-1\right)\left(2x-1\right)-\left(2x-1\right)\left(2x+1\right)=0\)
\(\left(2x-1\right)\left(2x-1-2x-1\right)=0\)
\(-2.\left(2x-1\right)=0\)
\(\Rightarrow2x-1=0\)
\(\Rightarrow x=\frac{1}{2}\)
vay \(x=\frac{1}{2}\)
d) \(x^2.\left(x^2+4\right)-x^2-4=0\)
\(x^2\left(x^2+4\right)-\left(x^2+4\right)=0\)
\(\left(x^2-1\right)\left(x^2+4\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x^2-1=0\\x^2+4=0\end{cases}}\Rightarrow\orbr{\begin{cases}x^2=1\\x^2=-4\end{cases}}\Rightarrow\orbr{\begin{cases}x=1hoacx=-1\\kotontai\end{cases}}\)
vay \(x=1\)hoac \(x=-1\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a ) \(x^2-25-\left(x+5\right)=0\)
\(\Leftrightarrow\left(x+5\right)\left(x-5\right)-\left(x+5\right)=0\)
\(\Leftrightarrow\left(x+5\right)\left(x-5-1\right)=0\)
\(\Leftrightarrow\left(x+5\right)\left(x-6\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x+5=0\\x-6=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=-5\\x=6\end{matrix}\right.\)
Vậy \(\left[{}\begin{matrix}x=-5\\x=6\end{matrix}\right.\)
b ) \(\left(2x-1\right)^2-\left(4x^2-1\right)=0\)
\(\Leftrightarrow\left(2x-1\right)^2-\left(2x-1\right)\left(2x+1\right)=0\)
\(\Leftrightarrow\left(2x-1\right)\left[\left(2x-1\right)-\left(2x+1\right)\right]=0\)
\(\Leftrightarrow\left(2x-1\right)\left(2x-2\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}2x-1=0\\2x-2=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}2x=1\\2x=2\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{1}{2}\\x=1\end{matrix}\right.\)
Vậy \(\left[{}\begin{matrix}x=\dfrac{1}{2}\\x=1\end{matrix}\right.\)
c ) \(x^2\left(x^2+4\right)-x^2-4=0\)
\(\Leftrightarrow x^2\left(x^2+4\right)-\left(x^2+4\right)=0\)
\(\Leftrightarrow\left(x^2-1\right)\left(x^2+4\right)=0\)
\(\Leftrightarrow x\left(x-1\right)\left(x^2+4\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=0\\x-1=0\\x^2+4=0\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=0\\x=1\\x^2=-4\left(VL\right)\end{matrix}\right.\)
Vậy \(\left[{}\begin{matrix}x=0\\x=1\end{matrix}\right.\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a,\(3x\left(x-1\right)+x-1=0\)
\(\Rightarrow3x\left(x-1\right)+\left(x-1\right)=0\)
\(\Rightarrow\left(3x+1\right).\left(x-1\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}3x+1=0\\x-1=0\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=-\dfrac{1}{3}\\x=1\end{matrix}\right.\)
c,\(\left(2x-1\right)^2-25=0\)
\(\Rightarrow\left(2x-1\right)^2=25\)
\(\Rightarrow\left(2x-1\right)^2=5^2\)
\(\Rightarrow2x-1=\pm5\)
\(\Rightarrow\left[{}\begin{matrix}2x-1=5\\2x-1=-5\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}2x=6\\2x=-4\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=3\\x=-2\end{matrix}\right.\)
![](https://rs.olm.vn/images/avt/0.png?1311)
b, x = -5/3 hoặc x = 4/3.
c, x = 0 hoặc x = 3, -3.
d, x = 0 hoặc x = 2, -2.
e, x = 1 hoặc x = \(\dfrac{-1}{2}\).
a: \(\Leftrightarrow x^2-40x+400-x^2-4x-3=-7\)
=>-44x+397=-7
=>-44x=-404
hay x=101
b: \(\Leftrightarrow\left[{}\begin{matrix}3x+5=0\\4-3x=0\end{matrix}\right.\Leftrightarrow x\in\left\{-\dfrac{5}{3};\dfrac{4}{3}\right\}\)
c: \(\Leftrightarrow x\left(x^2-9\right)=0\)
=>x(x-3)(x+3)=0
hay \(x\in\left\{0;3;-3\right\}\)
d: \(\Leftrightarrow x\left(x-2\right)\left(x+2\right)=0\)
hay \(x\in\left\{0;2;-2\right\}\)
e: =>(2x+1)(1-x)=0
=>x=-1/2 hoặc x=1
\(1-\left(x-2\right)^2=0\)
\(\Leftrightarrow1=\left(x-2\right)^2\)
\(\Leftrightarrow x-2=1\)
\(\Leftrightarrow x=3\)
\(\left(x+2\right)-\left(x+1\right)^2=0\)
\(\Leftrightarrow x+2=\left(x+1\right)^2\)
tự giải tiếp...............................